Strategi Peningkatan Wisatawan Domestik Bali Zoo Di Masa Pandemi Covid-19 - Rasidi, Rafny Alnovira; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 02 (2021): JISSOROT, 2022)
The decrease in the number of domestic tourists visiting has made the Bali Zoo management make a strategy to maintain and increase visits in the new normal era. This study uses rational choice theory by James S Coleman as a scalpel to analyze Bali Zoo’s strategy in increasing domestic tourist in the Covid-19 pandemic era. In this case, the Bali Zoo is able to utilize resources that have a purpose as expressed by various statements of informants. Namely, ticket pricing strategies considering the situation and conditions in the new normal era such as student promos, additional programs such as breakfast activities with orangutans, mandatory health protocols, and social media as an information center and media liaison between Bali Zoo and outsiders. Keywords : Strategy Bali Zoo, Traveller, Covid-19, Rational Choice